The embroidered closet : modern hand-stitching for upgrading and upcycling your wardrobe - Stratkotter, Alexandra (Abrams, 2022)
Perfect for all levels of stitchers, this instructional guide to garment embroidery, in which sustainability meets DIY, demonstrates how to embellish clothing through stylish and classic designs, and includes information on tools, techniques, and stitches.